Vegetable omega-3 and omega-6 fatty acids differentially modulate the antiviral and antibacterial immune responses of Atlantic salmon - Caballero-Solares, Albert; Eslamloo, Khalil; Hall, Jennifer R.; Katan, Tomer; Emam, Mohamed; Xue, Xi; Taylor, Richard G.; Balder, Rachel; Parrish, Christopher C.; Rise, Matthew L. (Scientific reports, 2024)
The immunomodulatory effects of omega-3 and omega-6 fatty acids are a crucial subject of investigation for sustainable fish aquaculture, as fish oil is increasingly replaced by terrestrial vegetable oils in aquafeeds. Unlike previous research focusing on fish oil replacement with vegetable alternatives, our study explored how the omega-6 to omega-3 polyunsaturated fatty acid (PUFA) ratio in low-fish oil aquafeeds influences Atlantic salmon's antiviral and antibacterial immune responses. Atlantic salmon were fed aquafeeds rich in soy oil (high in omega-6) or linseed oil (high in omega-3) for 12 weeks and then challenged with bacterial (formalin-killed Aeromonas salmonicida ) or viral-like (polyriboinosinic polyribocytidylic acid) antigens. The head kidneys of salmon fed high dietary omega-3 levels exhibited a more anti-inflammatory fatty acid profile and a restrained induction of pro-inflammatory and neutrophil-related genes during the immune challenges. The high-omega-3 diet also promoted a higher expression of genes associated with the interferon-mediated signaling pathway, potentially enhancing antiviral immunity. This research highlights the capacity of vegetable oils with different omega-6 to omega-3 PUFA ratios to modulate specific components of fish immune responses, offering insights for future research on the intricate lipid nutrition-immunity interplay and the development of novel sustainable low-fish oil clinical aquaculture feeds.